Differences Between U21 and U23 Semi-Professional Soccer Players in Perfectionism and Passion - Martín-Moya, Ricardo; Ogallar-Blanco, Adelaida Irene; García-Mármol, Eduardo; Liñán-González, Antonio; González-Fernández, Francisco Tomás (Physical Education Theory and Methodology, 2023)
Study purpose. The aim of this study is to analyse differences in perfectionism and passion and how these variables interact and might be expected to affect performance in U21 and U23 soccer players. Materials and methods. A total of 60 healthy semi-professional soccer players (age: 21.57±1.95 years; height: 179.76±5.79 cm) participated in the study. The participants were divided into two equal groups, one with those players younger than 21 years old and the other including players aged 21–23. This study was descriptive with a cross-sectional design and used the Frost Multidimensional Perfectionism Scale (FMPS) and Passion Scale questionnaires. Results. A paired-samples t-test was used for defining differences as a repeated measures analysis (U21 Group and U23 Group). Additionally, a t-test with data from the FMPS revealed significant differences in perfectionism global score, concern over mistakes, parental expectations, parental criticism, doubts about actions and organization. The participants were shown to be a heterogeneous group in both perfectionism and passion, with moderate perfectionistic characteristics, except for the personal standards subscale, in which the opposite trend was found. According to the outcomes obtained, the U21 group shows significant values in terms of the level of perfectionism. Conclusions. This research has highlighted the importance of addressing maladaptive perfectionism in interventions and support programs for athletes. Strategies such as promoting a growth mindset, encouraging self-compassion, and fostering a supportive and mastery-oriented environment have been suggested to help athletes manage perfectionistic tendencies and enhance their well-being and performance.